Harnessing artificial intelligence for safer medication practices / Mahmathi Karuppannan - Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
The Global Patient Safety Challenge: Medication Without Harm initiated by the World Health Organization, aims to reduce the level of severe, avoidable harm related to medications by 50% within a span of 5 years (1). Over the years, substantial progress has been made in improving medication safety, yet challenges persist (2). Majority of current patient safety approaches were developed prior to the healthcare digital revolution. Significant advances in healthcare practises can be achieved by adopting modern technological tools and digital advancements which hold the potential to substantially improve the prediction and prevention of patient safety risks.